Engineered mineralogical interfaces as radionuclide repositories - Douglas, Grant B.; Reddy, Steven; Saxey, David; MacRae, C.M.; Webster, N.A.S.; Beeching, L.J. (2023)
Effective capture of fugitive actinides and daughter radionuclides constitutes a major remediation challenge at legacy or nuclear accident sites globally. The ability of double-layered, anionic clay minerals known as hydrotalcites (HTC) to contemporaneously sequester a range of contaminants from solution offers a unique remedy. However, HTC do not provide a robust repository for actinide isolation over the long term. In this study, we formed HTC by in-situ precipitation in a barren lixiviant from a uranium mine and thermally transformed the resulting radionuclide-laden, nanoscale HTC. Atomic-scale forensic examination of the amorphized/recrystallised product reveals segregation of U to nanometre-wide mineral interfaces and the local formation of interface-hosted mineral grains. This U-phase is enriched in rare earth elements, a geochemical analogue of actinides such as Np and Pu, and represents a previously unreported radionuclide interfacial segregation. U-rich phases associated with the mineral interfaces record a U concentration factor of ~ 50,000 relative to the original solute demonstrating high extraction and concentration efficiencies. In addition, the co-existing host mineral suite of periclase, spinel-, and olivine-group minerals that equate to a lower mantle, high P–T mineral assemblage have geochemical and geotechnical properties suitable for disposal in a nuclear waste repository. Our results record the efficient sequestering of radionuclides from contaminated water and this novel, broad-spectrum, nanoscale HTC capture and concentration process constitutes a rapid solute decontamination pathway and solids containment option in perpetuity.